Working as a Healthcare Professional and Wellbeing During the COVID-19 Pandemic: Work Recovery Experiences and Need for Recovery as Mediators - Rus, Claudia Lenuţa; Oţoiu, Cătălina; Băban, Adriana Smaranda; Vâjâean, Cristina; Kassianos, Angelos P.; Karekla, Maria; Gloster, Andrew T. (Frontiers in Psychology, 2022)
Considering the high impact strain that the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has put on medical personnel worldwide, identifying means to alleviate stress on healthcare professionals and to boost their subjective and psychological wellbeing is more relevant than ever. This study investigates the extent to which the relationships between the status of working in healthcare and the subjective and psychological wellbeing are serially mediated by work recovery experiences and the need for recovery. Data were collected from 217 Romanian employees (44 health professionals and 173 employees from other domains) using a cross-sectional design with self-report instruments, during the first stage of the nationwide lockdown. The results of the serial mediation analyses revealed that working in the medical field is indirectly related to subjective and psychological wellbeing through the following: (i) mastery experiences and (ii) mastery experiences as an antecedent of the need for recovery. As such, our findings indicate that (i) working in the medical field is, in fact, linked to healthcare professionals’ subjective and psychological wellbeing, and they provide some input on (ii) how recovery experiences and the need for recovery intervene in these relationships. Based on these findings, theoretical, methodological, and practical implications were suggested, and future research directions were proposed to maximize healthcare professionals’ wellbeing.